1994
DOI: 10.1002/j.2161-0045.1994.tb00514.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self‐Efficacy Beliefs and Inventoried Vocational Interests

Abstract: It has generally been assumed that a linear relationship exists between vocational interests and self‐efficacy. Bandura (1986) suggested, however, that persons require some amount of reasonable challenge in activities to sustain their interest, and that the relationship of interest to self‐efficacy thus may be curvilinear. This research extended and remedied previous literature and tested explicitly Bandura's concept of a threshold. Results suggest general support for a linear relationship between interest and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 11 publications
(6 reference statements)
3
69
1
4
Order By: Relevance
“…Using Holland's hexagon theory (1997) as the framework, researchers have developed several measures to assess selfefficacy on each Holland theme. In general, findings suggested that males were significantly more confident in the Realistic and Investigative areas while females reported significantly greater Social confidence (Betz, Harmon, & Borgen, 1996;Lapan, Boggs, & Morrill, 1989;Lenox & Subich, 1994). The significant gender differences in favor of males on multicultural counseling self-efficacy found in the current study seemed to contradict with the above findings because counseling is classified as a Social occupation according to Holland's theory (Holland, 1996).…”
Section: Criterion Validity Of the Mcse-rd Scorescontrasting
confidence: 82%
“…Using Holland's hexagon theory (1997) as the framework, researchers have developed several measures to assess selfefficacy on each Holland theme. In general, findings suggested that males were significantly more confident in the Realistic and Investigative areas while females reported significantly greater Social confidence (Betz, Harmon, & Borgen, 1996;Lapan, Boggs, & Morrill, 1989;Lenox & Subich, 1994). The significant gender differences in favor of males on multicultural counseling self-efficacy found in the current study seemed to contradict with the above findings because counseling is classified as a Social occupation according to Holland's theory (Holland, 1996).…”
Section: Criterion Validity Of the Mcse-rd Scorescontrasting
confidence: 82%
“…Generally, increased self-efficacy may have a number of effects relevant to the expatriate situation. It may affect individuals' level of interest (Lenox and Subich 1994), contribution to their teams' effectiveness (Kozlowski, Gully, Nason and Smith 1999), setting of higher goals, and ultimately through higher performance (Locke, Frederick, Lee and Bobko 1984;Phillips and Gully 1997;Bandura 1989a, 1989b). Similarly, high levels of self-efficacy have been theorized to lead to positive choices (e.g.…”
Section: Self-efficacymentioning
confidence: 98%
“…Research investigating perceived self-efficacy and vocational interests includes gender differences for self-efficacy on Holland scales (Lenox & Subich, 1994), college students' perceived self-efficacy with respect to occupations representing Holland's six domains (Lapan, Boggs, & Morrill, 1989), and prediction of college majors by using Holland interest themes and general confidence themes (Betz, Harmon, & Borgen, 1996). However, there is a dearth of research investigating the link between teachers' vocational interests and self-efficacy perceptions in order to offset the teacher shortage, especially in the area of second language education.…”
Section: The Congruence Of Vocational Interests 12mentioning
confidence: 99%